Pengenalan aplikasi komputerisasi akuntansi untuk membantu Pembuatan Laporan Keuangan Usaha Kecil Cotton Supply - grace gata; Anita Diana; Ratna Ujiandari; Atik Ariesta (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2020)
Business financial statements are important for small businesses as one of the assessments for capital in formal credit institutions, because bookkeeping serves as a reference in business growth and development. Cotton Supply is a small entrepreneur who focused on the sale of sweaters, clothes and pants, located in Cipondoh Indah, Tangerang Banten, in the routine activities carried out by this business in recording still using notes in the form of handwriting that has a high risk of data recording errors, so that the final report produced is not in accordance with the reality of the data in the store. This becomes the background so that this community service activity is carried out with the aim to help facilitate and overcome the problems faced by Cotton Supply. The creation of this Financial Statement by using the accounting application MYOB which has facilities in data deposition until the creation of integrated financial statements in a short time so that it can manage the transactions carried out can be seen quickly. The first stage of this activity is to install the application followed by training on the use of modules, data entry and reading of the required financial statements. The results of Community Service activities by using the application of information systems in cotton supply small business is very helpful in solving the problems faced so far in making financial statements because it can be seen the growth and development of businesses that have been run and developed.